Withdrawal of Reports by Survivors of Sexual Violence Case Study: in The Central Kalimantan Polda - Mawarni, Mira; Kristian, Kristian; Sangalang, Rizki Setyobowo (Green Publisher Indonesia, 2025)
Sexual violence remains a pressing concern in Indonesia, with thousands of cases reported annually, yet only a fraction proceed to trial due to the withdrawal of reports by victims. This study investigates the factors that influence survivors of sexual violence to withdraw their legal complaints, and the subsequent impact on the legal process, particularly within the jurisdiction of the Central Kalimantan Regional Police. Employing an empirical juridical research method, this study collects data through in-depth interviews with survivors, police officers, and representatives from victim support institutions. The findings reveal that social stigma, fear of retaliation, distrust in the legal system, and insufficient legal or psychological support often lead victims to abandon legal proceedings. Despite the legal framework provided by Law No. 12 of 2022 on Criminal Sexual Violence, procedural barriers such as evidentiary requirements and inconsistent application of victim protection laws persist. The research underscores the need for a stronger integration of legal support mechanisms, survivor-focused policies, and community education to ensure justice. These findings contribute to understanding the real-world limitations of the TPKS Law's implementation and call for systemic reforms to support victims more effectively.